The AppSheet-Based Digital Attendance System Innovation to Improve Student Discipline Management - Darojah; Nurkolis; Lilik Ariyanto (Universitas Pendidikan Ganesha, 2025)
The problem of student discipline still relies on a manual attendance system, which often leads to delays, unexplained absences, and recording errors. This study aims to develop a digital attendance application and measure its levels of validity, superiority, and effectiveness in improving junior high school students’ discipline. The research employed the Research and Development (R&D) method using the ADDIE model. Data were collected through interviews, questionnaires, observations, and document analysis, with junior high school students as the research subjects. Data were analyzed using descriptive analysis and hypothesis testing, including expert validation tests, product practicality tests, one-sample t-tests, simple linear regression tests, paired t-tests, and N-Gain tests. The results showed that the AppSheet-based digital attendance system was effective in improving students’ attendance discipline and was superior to the manual attendance system. Although the results were not statistically significant in influencing students’ attendance discipline, the AppSheet-based digital attendance system was declared valid with a score of 98% and an average percentage of 92.31% (Very Good). The effectiveness level of this digital attendance system was categorized as high since the majority of students (60%) showed improved discipline. Therefore, it can be concluded that the product meets quality criteria in terms of content, appearance, and functionality, making it feasible to be used to enhance students’ attendance discipline. The novelty of this research lies in the use of the AppSheet application integrated with dual verification technologies—GPS and biometric verification—which has not been previously implemented.